2014
DOI: 10.1002/pen.23850
|View full text |Cite
|
Sign up to set email alerts
|

Alumina nanoparticle filled epoxy resin: High strain rate compressive behavior

Abstract: This study demonstrates high strain rate behavior of neat epoxy and epoxy resin reinforced with 2 wt% and 5 wt% alumina nanoparticles. The present study investigates effect of strain rate as well as effect of alumina nanoparticle dispersion on the compressive stress -compressive strain behavior of epoxy resin. Studies were carried out on compressive split Hopkinson pressure bar apparatus in the strain rate range of 700-3200 per sec. Significant enhancement of compressive strength of epoxy resin up to 147% was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Some authors have argued that the improvement in strength and brittleness tendency at high strain rates is attributed to the reduction of the mobility of thermoset polymer chains. Also, viscoelastic nature of the resin is believed to be responsible for the strength enhancement at high strain rates . Another remark adopted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have argued that the improvement in strength and brittleness tendency at high strain rates is attributed to the reduction of the mobility of thermoset polymer chains. Also, viscoelastic nature of the resin is believed to be responsible for the strength enhancement at high strain rates . Another remark adopted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So, the more energy required to initiate and propagate the crack in adhesive. Naik et al 36,37 reported that high strength of base (neat) adhesive under high loading rates occurred due to shear yielding, shear plugging mechanism, and formation of ring and radial cracks. The spherical shaped of nano‐Al 2 O 3 offered lower hindrance in cross‐linking of epoxy compared to nanorods.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the high cross-linking density, epoxy resins are generally very brittle with a very low fracture strain and have poor resistance to impact and crack propagation [2]. For this reason, efforts were made to improve the mechanical performance of the epoxy resins by the addition of different types of fillers, such as inorganic particles [3][4][5], elastomer particles [6,7], carbon nanotubes [8,9], hyperbranched polymers [10][11][12] and recently graphene nanoplatelets [2,13]. Compared to other filler types, silica nanoparticles are widely studied as fillers to epoxy resins.…”
Section: Introductionmentioning
confidence: 99%